(untitled) (World Science, 2022)
Background. Current data suggest that bone tissue produces hormonally active factors - modulators of metabolic processes throughout the body. The most significant osteoproteins is osteocalcin, the non-collagen structural protein of the bone matrix, which is synthesized by osteoblasts and enters the bloodstream during the resorption of bone tissue. Osteocalcin is involved in the regulation of energy balance, insulin secretion, peripheric insulin sensitivity, and adipocyte’s function, while being an important marker of bone remodeling. The aim of this study was to investigate the relationship between osteocalcin levels and metabolic parameters in 97 patients with type 2 diabetes over 50 years of age, in the course of pharmacotherapy using different classes of antidiabetic drugs, namely human insulin, glucagon-like peptide-1 agonists (aGLP), and sodium-glucose co-transporter 2 (SGLT2) inhibitors, depending on presence of obesity. Results. There was found the highest serum osteocalcin level in patients without obese who received a metabolically active therapy with insulin or aGLP-1, comparing to nonobese subjects of SGLT2 inhibitors therapy group. The lowest level of HbA1c and triglycerides observed in non-obese patients on the background of taking aGLP-1. Conclusion. It can be assumed that the factor determining the hypoglycemic efficacy of investigated drugs may be the pathogenesis of type 2 diabetes which depends on the degree of obesity, while the type of antidiabetic therapy has a corrective effect, probably mediated by changes in body weight and fat distribution.